Caffeine Promotes Global Spatial Processing in Habitual and Non-Habitual Caffeine Consumers - Giles, Grace E.; Mahoney, Caroline R.; Brunye, Tad T.; Taylor, Holly A.; Kanarek, Robin B. (Frontiers in Human Neuroscience, 2013)
Information processing is generally biased toward global cues, often at the expense of local information. Equivocal extant data suggests that arousal states may accentuate either a local or global processing bias, at least partially dependent on the nature of the manipulation, task and stimuli. To further differentiate the conditions responsible for such equivocal results we varied caffeine doses to alter physiological arousal states and measured their effect on tasks requiring the retrieval of local versus global spatial knowledge. In a double-blind, repeated-measures design, non-habitual (Exp. 1; N=36, M=42.5±29 mg/day caffeine) and habitual (Exp. 2; N=34, M=579.5±311.5 mg/day caffeine) caffeine consumers completed four test sessions corresponding to each of four caffeine doses (0 mg, 100 mg, 200 mg, 400 mg). During each test session, participants consumed a capsule containing one of the three doses of caffeine or placebo, waited sixty minutes, and then completed two spatial tasks, one involving memorizing maps and one spatial descriptions. A spatial statement verification task tested local versus global spatial knowledge by differentially probing memory for proximal versus distal landmark relationships. On the map learning task, results indicated that caffeine enhanced memory for distal (i.e. global) compared to proximal (i.e. local) comparisons at 100 (marginal), 200, and 400 mg caffeine in non-habitual consumers, and marginally beginning at 200 mg caffeine in habitual consumers. On the spatial descriptions task, caffeine enhanced memory for distal compared to proximal comparisons beginning at 100 mg in non-habitual but not habitual consumers. We thus provide evidence that caffeine-induced physiological arousal amplifies global spatial processing biases, and these effects are at least partially driven by habitual caffeine consumption.